Coating of adenovirus type 5 with polymers containing quaternary amines prevents binding to blood components - Subr, Vladimir; Kostka, Libor; Selby-Milic, Tom; Fisher, Kerry; Ulbrich, Karel; Seymour, Leonard W; Carlisle, Robert C (Journal of controlled release, 2009)
Adenovirus type 5 (Ad5) gene therapy vectors require protection against antibodies, complement proteins and blood cells if they are to be delivered intravenously to treat metastatic disease. Such protection can be achieved by chemically modifying Ad5 with polymers based on hydrophilic HPMA. Here, such polymers were designed to include side chains bearing reactive carbonyl thiazolidine-2-thione groups (TTs) to covalently modify available amino groups of the lysine residues in the Ad5 capsid. Furthermore, the inclusion of side chains bearing positively charged quaternary ammonium groups (QAs) was designed to improve electrostatic interaction of the polymers with negatively charged Ad5 hexon protein. Finally, to enable triggered uncoating and reactivation of the Ad5, either the TTs or both the TTs and the QAs were linked to polymer backbone via reductively degradable disulfide bonds. SDS-PAGE demonstrated that these polymers covalently modified Ad5 capsid proteins in a reduction reversible manner. In infection studies, polymers containing QAs prevented binding of coagulation factor X to Ad5. Furthermore, the antibody and complement mediated binding of Ad5 to erythrocytes was reduced by such polymers (>95% without polymer, 25% following coating). These data indicate that coating Ad5 therapeutics with such polymers will improve blood circulation half-life and deposition at disease sites.
Keywords: Complement System Proteins; genetická terapie; aminy; Cell Line, Tumor; adenovirové infekce; luciferasy; statická elektřina; Silver Staining; erytrocyty; vazba proteinů; Molecular Structure; Capsid Proteins; imunologické faktory; Polymers; lidé; Antibodies; Factor IX; Adenoviridae Infections; faktor IX; Amines; molekulární struktura; genetické vektory; molekulová hmotnost; Immunologic Factors; Erythrocytes; virové plášťové proteiny; Luciferases; polymery; barvení stříbrem; Static Electricity; Adenoviridae; Genetic Therapy; Molecular Weight; Genetic Vectors; Protein Binding; komplement; protilátky; nádorové buněčné linie; Humans